Last dance, last chance : [compact disc, unabridged] : and other true cases - Rule, Ann (Rule, Ann. Ann Rule's crime files, 2013)
The riveting case of a fraudulent doctor whose lifelong deceptions had deadly consequences. Dr. Anthony Pignataro was a cosmetic surgeon and a famed medical researcher whose flashy red Lamborghini and flamboyant lifestyle in western New York State suggested a highly successful career. But appearances can be deceiving - and, for the doctor's wife, very nearly deadly.